Estudo do papel do contexto facilitador, segundo diferentes abordagens teóricas, na aquisição do R-fraco por crianças com desvio fonológico - Checalin, Mardonia Alves (2008)
The aim of this research was verify the applicability of the favorable and neutral environments, got from data of children speech without change of language, in the treatment of children with Articulatory Disorders (AD). The diagnosis of AD was obtained through phonological and complementary assessments. The study participants were seven children of both sexes, with an average age of six years. The inclusion criterion was that present, among the assessments made, changed result only in the phonological assessment, have missing in the phonological inventory only the phoneme /r/, being monolingual speaker of Brazilian Portuguese and not have received prior speech therapy care. All the subjects received treatment for speech for AD through the ABAB - Withdrawal and Multiple Probes Model, six had the /r/ treated in Onset Medial (OM) and the two had /r/ treatment in Coda Medial (CM). In OM, was studied the favorable environment according to surveys conducted through generative, hand and neutral theoretical approach. In CM, was the studied favorable environment and neutral, according to a survey conducted in generative approach. From the results of treatment, a description and an analysis of the evolution therapy were made. Data analysis was performed through the transcripts of phonological assessments made before, during and after the therapy intervention. After comparing the results of assessments among the subjects in an attempt to identify the effectiveness of treatment, using the context in the AD and among the theoretical approaches, that who promote more changes in the phonological system of the subject. The results were not conclusive in relation to the most effective environment in the treatment of AD, but indicated both in OM and in CM, that the neutral context was more efficient than the favorable. These results led to interest in investigating, in the speech subject data, the possibility of establishing new contexts based on speech children data with AD. After the analysis of lexical items produced correctly by seven subjects of this research, were identified different contexts of those used in the words-target of the treatment. This finding suggests that the favorable linguistic context, based on data from normality, not be applicable to children with AD. It is suggested a research with speech children data with AD to suggest new linguistic contexts to be used in speech therapy to promote the acquisition of the phoneme earlier.